Indoor navigation system using Dijkstra’s algorithm for emergency situation: article / Mohd Faizulhayad Mashuri - Mashuri, Mohd Faizulhayad (2015)
This paper will discuss on an implementation of route planning in Indoor Navigation System (INS) for emergency situation. Global Positioning System (GPS) cannot be used for INS since signals sent by satellites cannot penetrate the construction materials inside a building. Wireless Fidelity (Wi-Fi) is the system that can make INS possible. By implementing Radio Signal Strength (RSS) provided by Wireless Fidelity (Wi-Fi) where most building already have it, Reference Points (RP)s with it designated RSS can be setup across the area desired. The connection or paths between each RP can be created to create the best route to the destination. The technique used for the route planning is Dijkstra’s algorithm. The result of this technique shows higher accuracy in terms of shortest distance taken to the destination compared to other technique and the implementation of this technique are easy since users only have to manipulate the weight between each RPs according to obstacle that exist along the paths. Bigger obstacles will gives higher value of weight. Route planning using Dijkstra’s algorithm can produce better accuracy and more reliable in indoor environment since the only factor taken into account is the weight for each path.